Problem Based Learning with Video for Religious and Social Values: Problem Based Learning Berbasis Video untuk Nilai Religius dan Sosial - Kartika, Amalia Dwi; Sholikhah, Khotimatus; Fauziyah, Nina Rohmatul (Academia Open, 2026)
General Background: Civic Education plays a strategic role in developing students’ religious values and social attitudes at the elementary level. Specific Background: However, the learning process often relies on conventional methods, making abstract values difficult for students in the concrete operational stage to understand and internalize. Knowledge Gap: There is limited focus on how Problem Based Learning integrated with audiovisual media supports the internalization of both religious and social values beyond cognitive outcomes. Aims: This study aims to analyze the implementation of video-assisted Problem Based Learning in Civics Education for fostering religious values and social attitudes among third-grade students at MI Darul Ulum Jotosanur. Results: The findings indicate that video-based Problem Based Learning increases student engagement, critical thinking, collaboration, and the ability to relate values to real-life contexts, although challenges arise from teacher readiness, student ability differences, time limitations, and environmental support. Novelty: The study highlights the integration of Problem Based Learning with audiovisual media to emphasize value internalization through real problem-solving experiences in elementary students. Implications: The study suggests that teachers design contextual Problem Based Learning supported by visual media and consistent reflection, along with collaboration between schools and parents, to support character formation in students. Highlights• Video-supported problem scenarios stimulate active participation and classroom interaction• Contextual tasks guide learners to connect moral concepts with daily behavior• Implementation constraints emerge from pedagogical readiness and learning conditions KeywordsCivic Education; Problem Based Learning; Religious Values; Social Attitudes; Video Media